Comparison of concurrent chemoradiotherapy with radiotherapy alone for locally advanced esophageal squamous cell cancer in elderly patients: A randomized, multicenter, phase II clinical trial. Issue 4 (27th April 2022) - Liu, Yanxiao; Zheng, Zhiyong; Li, Minghao; Zhang, Yaowen; Zhao, Fujun; Gong, Heyi; Lin, Haiqun; Huang, Wei; Chen, Xiangming; Xu, Zhiqiao; Li, Xiaomin; Liu, Wenzhi; et al.
Abstract: This randomized, multicenter, phase II clinical trial was performed to compare the safety and efficacy of concurrent chemoradiotherapy using S‐1 (CCRT) with radiotherapy alone (RT) for elderly patients with locally advanced esophageal squamous cell carcinoma (ESCC). All eligible patients were randomly assigned to the CCRT group or the RT group at a 1:1 ratio. The CCRT group received 50.4 Gy radiotherapy concurrent with S‐1 and the RT group received 59.4 Gy radiotherapy alone. The primary endpoints were toxicity and the overall response rate (ORR), and the secondary endpoints were overall survival (OS) and progression‐free survival (PFS). In total, 157 elderly patients with ESCC were recruited from December 2016 to March 2020. By June 2021, the median follow‐up duration had reached 38 months. No grade 5 toxicities occurred in either group and the overall rate of severe toxicities (≥grade 3) was higher in the CCRT group (19.2% vs 7.6%; P  = .037), particularly neutropenia (7.7% vs 1.3%; P  = .06). The CCRT group presented a significantly higher ORR (83.3% vs 68.4%; P  = .009) and prolonged PFS (25.7 vs 13.9 months; P  = .026) than the RT group. The median OS was 27.3 months in the CCRT group and 19.1 months in the RT group ( P  = .59). For patients older than 70 years with locally advanced ESCC, concurrent chemoradiotherapy with S‐1 had tolerable adverse effects and improved ORR and PFS compared to radiotherapy alone. Abstract : What's new? Many elderly patients with esophageal squamous cell cancer (ESCC) cannot tolerate standard concurrent chemoradiotherapy (CCRT), necessitating a search for less‐toxic, but equally effective alternative therapies. In this trial, the authors compared the safety and efficacy of CCRT, combined with the fluorouracil drug S‐1, to radiotherapy alone in elderly patients with locally advanced ESCC. CCRT with S‐1, with a radiation dose of 50.4 Gy, was well‐tolerated in elderly patients. Moreover, compared with radiotherapy alone, short‐term tumor response and progression‐free survival were significantly higher with CCRT and S‐1. The findings suggest that CCRT is both safe and effective in elderly ESCC patients.